Impact analysis of electric vehicles charging on the Icelandic Power System - Winnie Adhiambo Apiyo 1986- (2019)
Increased adoption of electromobility in the form of Battery Electric Vehicles and Plug-in Hybrid Electric Vehicles is anticipated in Iceland over the next few years. Electrified transport will lead to increases in system peaks that are higher than the corresponding increases in annual electricity demand. The objective of this study is to assess the likely incremental impact of EVs on both the transmission and distribution networks through evaluating the network reinforcements needed to support the increase in electricity demand and quantify associated costs. This is done by extensive analyses of large datasets of the transmission and distribution grids and transportation data. The country depends on imported petroleum fuels to meet its transport fuel demand. Transition to EVs is of particular interest for Iceland as electricity can be supplied from low cost clean renewable energy resources. To evaluate how the transition to EVs will impact the system maximum load, four load profiles are defined: BAU, PROPOSAL, PREMIUM and BAN scenarios. The load profile models used for scenario analysis is done by incorporating key fiscal parameters including different taxes on vehicle usage pattern and upfront purchase cost, petroleum fuel tax levies, vehicle tax exempting, extra fees and subsidies. Realistic charging profiles of EVs are based on real-life driving data from different traffic zones. The fleet number in each area is estimated based on the population and commercial density of electricity consumption in the regions. This EV load growth is studied in three different loads forecasted assumptions or scenarios: Base case scenario, Upgraded system scenario and the slow progress energy forecast scenario. The scenarios are analysed using two separate Icelandic power system models. The reinforcement needs are quantified for up to 32 years. The year 2018 is assumed to be the first year PHEVs and BEVs are implemented, while 2050 would allow the sufficient technology time to penetrate the Icelandic vehicle fleet fully. The ...